Amendments to the Patients’ Rights and Patients’ Spokesman Rights Act. A few remarks on the mechanisms of awarding compensation for damage or injury caused by medical occurrences - Białkowski, Michał (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The objective of this paper is to present the amendments to the Patients’ rights and Patients’ Rights Spokesman Act of 28 April 2011. The paper focuses on the drawbacks of the provisions of the Act concerning claims for compensation for damage or injury caused by medical occurrences that are put before regional medical occurrences committees. Despite the undoubtedly right direction of the amended legislation, the purpose of the amendments has not been achieved. The renouncement by applicants of all the claims when accepting the insurers offer concerning the amount of compensation, low sums of the compensation which the patient or his heir may be awarded as well as restricting the places where medical occurrences may happen only to hospitals, narrow the applicability of the amendments and warrants further work on the existing solution.